2022
DOI: 10.1002/cpz1.505
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Precision‐Cut Lung Slices for Studying Innate Immunity to Viral Infections

Abstract: Precision-cut lung slices (PCLS) are a novel tool to study cells of the lower airways. As PCLS retain the integrity and architecture of the lung, they constitute a robust model for studying the cells of the lower respiratory tract. Use of PCLS for imaging has been previously documented; however, other applications and techniques can also be applied to PCLS to increase their use and therefore decrease the number of animals needed for each experiment. We present a detailed protocol for generating PCLS from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In this study, we maintained the PCLS up to 96 h without significant reduction in cell viability. Other studies have shown viable PCLS for up to 8 days in culture ( Alsafadi et al, 2020 ; Michalaki et al, 2022 ). If prolonged culture of PCLS is required to observe long-term effects of gene ablation or overexpression, embedding PCLS in hydrogel has been shown to effectively extend their viability for at least 3 weeks ( Bailey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, we maintained the PCLS up to 96 h without significant reduction in cell viability. Other studies have shown viable PCLS for up to 8 days in culture ( Alsafadi et al, 2020 ; Michalaki et al, 2022 ). If prolonged culture of PCLS is required to observe long-term effects of gene ablation or overexpression, embedding PCLS in hydrogel has been shown to effectively extend their viability for at least 3 weeks ( Bailey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…An alternative option to assess the efficiency of Vangl2 allele recombination would have been to evaluate VANGL2 protein levels by immunostaining or western blotting; however, it is very challenging to obtain VANGL2 protein data owing to a lack of effective and/or specific antibodies ( Belotti et al, 2012 ), but this is a viable alternative to evaluate recombination efficiency of other targets of interest. In the future, flow cytometry could be explored as an alternative to immunostaining for validation and quantification of Cre-mediated recombination efficiencies in tissue slices ( Michalaki et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other issues concern standardization of experimental conditions among laboratories. Multiple methodsfocused papers have been published detailing the processing of mainly murine [66,[300][301][302][303] and human lung tissue [258,304], highlighting both the complexities of generating PCLS and noting that becoming adept at the process of generating the slices can ensure greater reproducibility of results. These and other publications also show the differences in how murine PCLS are generated versus human PCLS, and demonstrate that the method(s) of generation even the same type of lung source (i.e.…”
Section: Advantages and Challenges Of The Systemmentioning
confidence: 99%
“…PCLS (4mm diameter) were snap frozen using liquid nitrogen and were stored at -80°C until extraction. PCLS RNA isolation protocol was adapted from previously published studies [27,28].…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%
“…Additionally, extracting adequate amounts and quality of RNA from PCLS has been reported as a challenge due to limitations of small tissue mass and interference from agarose [27,29]. Using a modified protocol derived from Stegmayr et al (2020) [27] and Michalaki et al (2022) [28], we isolated RNA using 6 pooled PCLS per condition (see Methods).…”
Section: Development Of Optimized Pcls Experimental Workflowmentioning
confidence: 99%